2022
DOI: 10.1084/jem.20221334
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in TB research

Abstract: Tuberculosis (TB) is an infectious disease bedeviled by complexity. This poses myriad challenges for a research ecosystem organized around specialist host- and/or pathogen-focused thrusts. Here, we highlight the key challenges and their implications for developing new tools to control TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 5 2022 Tuberculosis prevalence: beyond the tip of the iceberg Novel stages and disease thresholds for TB Perspective Scriba et al. 54 2022 Challenges in TB research Challenges in developing new diagnostics and vaccines for TB control Perspective Yoon et al. 55 2022 CT and 18F-FDG PET abnormalities in contacts with recent tuberculosis infections but negative chest X-ray Systematic review of CT and PET-CT imaging of asymptomatic TB contacts with normal X-rays Systematic review Sossen et al.…”
Section: Resultsmentioning
confidence: 99%
“… 5 2022 Tuberculosis prevalence: beyond the tip of the iceberg Novel stages and disease thresholds for TB Perspective Scriba et al. 54 2022 Challenges in TB research Challenges in developing new diagnostics and vaccines for TB control Perspective Yoon et al. 55 2022 CT and 18F-FDG PET abnormalities in contacts with recent tuberculosis infections but negative chest X-ray Systematic review of CT and PET-CT imaging of asymptomatic TB contacts with normal X-rays Systematic review Sossen et al.…”
Section: Resultsmentioning
confidence: 99%
“…When an individual is infected with Mtb, the actual infection dose may be much lower than the number of bacteria released by coughing because not all aerosols generated by the infected person are inhaled. In addition, it has been reported that symptomatic TB patients release Mtb aerosols not only by cough but also by exhalation, with an aerosol size of 0.5-5 μm, showing that actual infection can be achieved in the context of a sustained low-dose of bacteria ( 21 , 22 ). However, animal models for vaccine research in the preclinical stage can be established through a single, sufficient infection dose and used to evaluate vaccine efficacy.…”
Section: The Second Hurdle: a Gap Between Experiments And The Natural...mentioning
confidence: 99%
“…A deeper understanding of the disease's behavior and pathogenesis has uncovered more challenges for TB research toward elimination (14). An interesting and shocking observation from TB aerobiology studies was the occurrence of MTB transmission even with tidal breathing (15).…”
Section: Introductionmentioning
confidence: 99%